2011
DOI: 10.1007/s11655-011-0788-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of San’ao Decoction (三拗汤) on the airway inflammation and hyperresponsiveness in a murine model of lipopolysaccharide-enhanced asthma

Abstract: SAD has a good therapeutic effect on airway hyperresponsiveness in the LPS-enhanced asthma model, but its definite influence on airway inflammation is not remarkable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…[26] The pathologic mechanisms of asthma include allergic reaction, bronchial chronic inflammation, airway hyperresponsiveness, abnormality of airway neuromodulation, genetic factor, respiratory viral infection, neural signal transduction mechanism, and airway remodeling. [23,27]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26] The pathologic mechanisms of asthma include allergic reaction, bronchial chronic inflammation, airway hyperresponsiveness, abnormality of airway neuromodulation, genetic factor, respiratory viral infection, neural signal transduction mechanism, and airway remodeling. [23,27]…”
Section: Discussionmentioning
confidence: 99%
“…[1719] Recently, with the publication of a number of trials on SAD for asthma, they have proved that SAD has good clinical effect. [2023] There is an urgent need for a systematic review to support the effectiveness and safety of SAD in treating asthma. Hereby, the purpose of the study is to systematically review current available articles to assess the efficacy and safety of the SAD treatment in patients of asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Rhizoma Pinelliae (Ban Xia) inhibits TNF- α -induced NF- κ B activation [53], and the extraction from Poria (Fu ling) has immunoregulatory effect [54]. In addition, San'ao decoction, a famous Chinese medicine formula composed of three herbs identified in the study, Semen Armeniacae Amarum (Xin Ren), Radix Glycyrrhizae (Gan Cao), and Herba Ephedrae (Ma Huang), has shown anti-inflammation and hyperresponsiveness in airway of a murine model [55]. …”
Section: Discussionmentioning
confidence: 99%
“…SAD may have a inhibitory effect on airway inflammation of asthmatic rats by regulating Th1/Th2 transfer factors [ 9 ]. Our recent research showed that SAD and its series of formulae could alleviate normal human bronchial epithelial cell damage and suppress airway inflammation by various ways [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%